Analog BiCMOS Design: Practices and Pitfalls - Daly, James C. (Cisco Press, 2011)
Integrated circuits (ICs) don't always work the first time. Many things can and do go wrong in analog circuit designs. There are a number of common errors that often require costly chip redesign and refabrication, all of which can be avoided when designers are aware of the pitfalls. To realize success, IC designers need a complete toolbox-a toolbox filled not only with a solid background in electronics, design concepts and analysis skills, but also with the most valuable tool of all: experience.